Self-Monitoring Home Blood Pressure in Community-Dwelling Older People: Age Differences in White-Coat and Masked Phenomena and Related Factors—The SONIC Study - Jinmei Tuo; Kayo Godai; Mai Kabayama; Yuya Akagi; Hiroshi Akasaka; Yoichi Takami; Yasushi Takeya; Koichi Yamamoto; Ken Sugimoto; Saori Yasumoto; Yukie Masui; Yasumichi Arai; et al. (International Journal of Hypertension)
Some studies reported that home blood pressure (HBP) monitoring was conducted by community-dwelling older people themselves, but there have been few studies on HBP including very old populations aged over 90 years old. Thus, the aim of the present study was to clarify the current situation of white-coat and masked phenomena defined by on-site and home BP measurements in community-dwelling old and oldest-old populations. The study subjects were 380 participants from the SONIC study, a cohort study of a community-dwelling old population, who measured their HBP in a series of 3–5 days by themselves and brought their HBP records to the venue on the survey day. Study participants’ characteristics were as follows: female, 185 (48.7%); male, 195 (51.3%); 70s, 95 (25.0%); 80s, 245 (64.5%); and 90s, 40 (10.5%). A total of 344 (90.5%) participants had hypertension. A total of 291 (76.6%) hypertensive participants taking antihypertensive medication were analyzed in the present study. Regarding the types of hypertension defined by home and on-site BP, they showed white-coat phenomenon, 183 (48.2%); masked phenomenon, 115 (30.3%); sustained hypertension, 130 (34.2%); and normotension, 82 (21.6%). On comparison of age groups, there was a tendency for the white-coat phenomenon to be common in young-old people in their 70s and the masked phenomenon to be common in very old people in their 90s. Therefore, since the detection of white-coat and masked phenomena is closely associated with appropriate BP management, it is very important for community-dwelling older populations to self-monitor HBP.